Um "mestiço irrecusável": Tito Lívio de Castro e o pensamento cientificista no Brasil do século XIX - Ana Maria Araujo de Almeida (2008)
The present dissertation is a study about Tito Lívio de Castro's trajectory (from 1864 to 1890) based on the analysis of his work produced in Brazil in the last decades of the 19th Century. Strongly influenced by the evolutionist theories that were popular at this time, Castro's work represents the political, scientific and cultural moment that the lastBrazilian decades witnessed in the 19th Century. Castro produced several essays on Brazilian reality, mentioning a lot in his writings some matters like race, crossing of races, literature and education. Besides, he accomplished a very specific study about women and her biological and social role in the development of the Brazilian nation. He defended the female access to education and at the same time he accomplished a significant report on the educational situation in Brazil. We will seek to correlate the author's life and work in order to understand the environment in what his ideas came up, as well as the speeches included there and the meanings that they ought to express.